Nasal carriage of Staphylococcus aureus among indigenous people of Toba Qom ethnic, Benjamín Aceval, Paraguay - Norberg, Paulo Roberto Blanco Moreira; Villalba, Maria Laura Meister; Ortellado, Larissa Duarte; Coronel, Marcelo; Ribeiro, Paulo César; Norberg, Antonio Neres (International Journal Of Community Medicine And Public Health, 2018)
Background: Staphylococcus aureus are Gram positive cocci components of the normal microbiota of the skin and mucosa, but can attack other sites of the organism depending on favourable conditions. The condition of host of this bacterium colonizing the nasal mucosa is recognized as a potential risk factor for subsequent invasive infections. This research had the objective to investigate the prevalence of nasal carriers of S. aureus among Toba Qom indigenous ethnic group of the San Francisco de Asis community, Paraguay, and to determine the sensitivity profile to antimicrobial agents. Methods: 141 samples of the nasal cavities were analyzed. Isolation and identification were performed by conventional microbiological methods, by the staining characteristics of the Gram method, catalase and coagulase tests, mannitol fermentation test and deoxyribonuclease test. Antimicrobial susceptibility test was performed by the agar diffusion technique according to a procedure standardized by the National Committee for Clinical Laboratory Standards. Results: 22 of the 141 individual examined samples were colonized by Staphylococcus aureus, which corresponds to a prevalence of 15.6%. Conclusions: Multidrug-resistant strains were not isolated. All samples presented good sensitivity to most antibiotics except for nalidixic acid, which all samples presented resistance.